Determination Some Creep Factors For Lead Under Tension - Tariq Mohammed Ali Al Nuaimi (Engineering and Technology Journal, 2015)
There are a lot of engineering structures working at elevated temperatures for long periods, as in chemical plants, generation, transfer and energy application or devices uses of energy, such as turbines and reactors. When those parts work at high temperature, it was found that their materials which exposed to loads will undergo to plastic deformation and deforms slowly like a crawl turtle, for this reason they named this slow deformation as a Creep.Care has been given in this research has to study the issue of creep under the influence of various loads under certain temperature, and the implementation of a creep test machine by a tension samples made from lead .This research includes a study of creep parameters under the influence of temperatures. Creep properties were investigated under constant stress and fixed temperature in terms of the relation between a strain for period of times by the specimen used in this study which was lead and the applied load was tension.